Membrane protein solubilization and structure determination using de novo–designed proteins - Ljubica Mihaljević; David E. Kim; Pooja D. Bandawane; Helen E. Eisenach; Andrew J. Borst; Alexis Courbet; Connor Weidle; Kenneth D. Carr; Everton Bettin; Qiushi Liu; Aldo T. Trejos; Sagardip Majumder; et al. (Science, 2026)
Developing therapies and vaccines against integral membrane proteins is hindered by their extensive hydrophobic surfaces, which complicate production and structural analysis. Here, we describe a general deep learning–based design approach for solubilizing native membrane proteins while preserving their sequence, fold, active-site, and ligand-binding properties. Genetically encoded de novo protein WRAPs [water-soluble RFdiffused amphipathic proteins] surround the lipid-interacting hydrophobic surfaces, rendering them thermostable and water-soluble without the need for detergents. We design WRAPs for both monomeric and oligomeric beta-barrel outer membrane proteins and helical multipass transmembrane proteins. A 2.95-angstrom-resolution cryo–electron microscopy structure of WRAPed mycobacterial porin demonstrates that WRAPs can be used for the structural determination of membrane proteins in solution. As a step toward syphilis vaccine development, we generated soluble versions of Treponema pallidum antigens.